Transforming UMPSAs Reading Habits The Reading Circle Programme Chronicles - Farah Liyana, Ahmad Azmey; Hanisah, Kasbon; Azimah, Ahmad Zaki; Nur Syafawati, Sabuan (UMPSA, 2023)
Reading is one of the most important skills that students need to succeed in their academic and professional lives. However, in an age dominated by digital distractions and the ever-growing allure of bite-sized information, students are gradually veering away from the age-old practice of reading. This has far-reaching consequences, affecting not only academic performance but also the development of critical thinking and analytical skills.